Data security using random dynamic salting and AES based on master-slave keys for Iraqi dam management system - Hussam J. Ali; Talib M. Jawad; Hiba Zuhair (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In the present time, dam management is considered one of the important challenges for e-government in Iraq, becuase it needs information technology infrastructure, data integrity and protection of user privacy against Internet threats that render such vital infrastructure ineffective. This struggle between the proposed dam management system (DMS) and a multi-tier secure model specifically for the Fallujah dam (and generally for all dams) which is addressed in this paper as a case study. To do this, a relational database design will discuss the development of a multi-tier secure model for integration of the dam management framework with its functions. This paper will discusse encryption and decryption of the dam data using the advanced encryption standard (AES) algorithm with derived keys via PBKDF2 and RNG sequences generator and Slave key for salting protection. The experimental results and analysis on the speed of encryption/decryption process, entropy value, plain text sensitivity, key sensitivity, keyspaceanalysis and histogram analysis will prove the the proposed scheme can impede the known attacks like brute force attacks, statistical and differential.Thus, the encryption scheme can be implemented on the proposed DMS and any other information system, as the implementation which will be presented in the results.